2020
DOI: 10.1101/2020.03.24.005355
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tumor MHCII immunity requires in situ antigen presentation by cancer-associated fibroblasts

Abstract: Author contributions: Conception and design study, M.T.; Development of methodology, M.T.;Acquisition of data, D.K., K.G., E.A., P.S., A.P. and M.T.; Analysis and interpretation of data, D.K., K.M.V., C.T., and M.T.; Providing human samples, I. ABSTRACTIn situ antigen presentation is required to sustain active proliferating CD4 + T cells in tumours and to help form memory CD8 + T cells, but the antigen presenting cells (APCs) and pathways involved remain elusive.Cancer associated fibroblasts (CAFs) are promine… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…scRNA-seq of samples from patients with ICC revealed a subpopulation expressing MHC class II-related genes such as CD74 , HLA-DRA and HLA-DRB1 54 . A recent study suggested that dense apCAF regions in human lung tumors define immunologically active regions with increased CD4 + T cell infiltration 91 . Leveraging published scRNA-seq data 37 and a defined metric for assessing physiologically relevant MHC class II gene expression, this study defined a population of potential apCAFs in human lung cancer and in mice, and proposed alveolar epithelial cells as their potential origin.…”
Section: Antigen Presenting Cafsmentioning
confidence: 99%
See 1 more Smart Citation
“…scRNA-seq of samples from patients with ICC revealed a subpopulation expressing MHC class II-related genes such as CD74 , HLA-DRA and HLA-DRB1 54 . A recent study suggested that dense apCAF regions in human lung tumors define immunologically active regions with increased CD4 + T cell infiltration 91 . Leveraging published scRNA-seq data 37 and a defined metric for assessing physiologically relevant MHC class II gene expression, this study defined a population of potential apCAFs in human lung cancer and in mice, and proposed alveolar epithelial cells as their potential origin.…”
Section: Antigen Presenting Cafsmentioning
confidence: 99%
“…Since such treatment promotes accumulation of immune suppressive inflammatory CAFs, dual treatment with checkpoint inhibitors may provide important additive effects. c Enhancing the activity of antigen presenting CAFs and their ability to recruit CD4+ T cells 91 could promote anti-tumor immune activity. d Targeting inflammatory CAFs with IL1R antagonists (e.g.…”
Section: Figurementioning
confidence: 99%